Phenology of Gonystylus bancanus in Pahang, Peninsular Malaysia - Parlan, Ismail; Mohd Said, Mohd Nizam; Mohamad, Abdul Latiff; Ibrahim, Faridah Hanum; Ibrahim, Shamsudin (Forest Research Institute Malaysia, 2011)
A study on the phenology of Gonystylus bancanus (ramin melawis) was conducted in Pekan Forest Reserve, Pahang, Peninsular Malaysia, which covers areas of virgin and logged-over forests. Observations revealed that the flowering of G. bancanus was supra-annual. The smallest G. bancanus tree to flower was 29 cm in diameter at breast height (dbh) and was located in a logged-over site. Most trees that flowered had larger dbh of more than 40 cm and were found in logged-over and virgin forests. A total of 71-86 days was recorded for full development from the budding stage to mature fruit formation. The budding phase was quite long, extending for more than a month. However, it took only about two weeks for the flowers to become fruits. The flowers of G. bancanus were pollinated by thrips (Heterothripts sp.) and stingless bees (Trigona canifrons and T. laeviceps), while aphids (Aphis sp.), Prevost's squirrels (Callosciurus prevostii) and plantain squirrels (C. notatus) were identified as predators of G. bancanus flowers and fruits. Gonystylus bancanus seeds were mainly dispersed by gravity but the Malayan flying fox (Pteropus vampyrus) was also observed to disperse the fruits. Other fruit bats, namely, Cynopterus sphinx, Megaerops ecaudatus and Penthetor lucasi were also identified as potential seed dispersal agents of G. bancanus.